PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA KOPERASI MITRA ANAK RANTAU DI KELURAHAN KEDAUNG BARAT KECAMATAN SEPATAN TIMUR KABUPATEN TANGERANG - Ritani ndruru, koverlius buulolo (Universitas Tangerang Raya, 2024)
Abstract: The problems observed in this research are lack of incentives or unfair compensation, decreased employee work motivation, and decreased work productivity. This research aims to determine the influence of compensation and motivation on employee performance at the Mitra Anak Rantau Cooperative in Kedaung Barat Village, East Sepatan District, Tangerang Regency. The research method used was quantitative, sampling 50 people using saturated samples. The research results are explained by the regression equation Y = 16.664+0.393 Which means that there is a partial positive and significant influence between Compensation on Employee Performance at the Mitra Anak Rantau Cooperative in Kedaung Barat Village, East Sepatan District, Tangerang Regency. From the results of research based on analysis of research data, the relationship between Compensation and Motivation on Employee Performance at the Mitra Anak Rantau Cooperative in Kedaung Barat Village, East Sepatan District, Tangerang Regency can be explained. This can be explained by the regression equation Y = 16.664+0.393 X1 + 0.303X2 +e and tcount > ttable or (2.256>2.01174) H02 is rejected and H2 is accepted with a Sig value of 0.029 < 0.05. Which means that there is a partial positive and significant influence between Motivation on Employee Performance at the Mitra Anak Rantau Cooperative in Kedaung Barat Village, East Sepatan District, Tangerang Regency. From the results of research based on analysis of research data, the relationship between Compensation and Motivation on Employee Performance at the Mitra Anak Rantau Cooperative in Kedaung Barat Village, East Sepatan District, Tangerang Regency can be explained. This can be explained by the regression equation Y = 16.664+0.393 X1 + 0.303X2+e and Fcount value >F table (16,755 >3.20) H03 is rejected and H3 is accepted with a Sig value of 0.029<0.05. Which means that there is a simultaneous positive and significant influence between compensation and motivation on employee performance at the Mitra Anak Rantau Cooperative in Kedaung Barat Village, East Sepatan District, Tangerang Regency